The Analysis Of Hydrology In Comal River - Gunawan Gunawan; Saihul Anwar; Ohan Farhan (Journal of Green Science and Technology, 2019)
This research was conducted to find out the availability of water to the requirements of water and also predict flood plan discharge for return period based on hydrological analysis in Comal River.Calculations are carried out using rainfall data obtained from PUSDATARU of Pemali - Comal from 1999 - 2017.Used the rainstation in the region of Comal Watershed, there are 7 rain stations. Catchment area of rain station used Thiessen Polygon Method to know value of catchment area of each rain station. The Gumbel distribution (Generalized Extreme Value distribution Type-I) is used to model the distribution of the maximum (or the minimum) of a number of samples of various distributions. The calculation of the flood discharge design is using the Nakayasu, Rational, Weduwen, Weduweden, and Haspers method.Based on the result of this research it can be concluded that the biggest water potential occurs in January is 199.60 m3/s and the smallest in August is 0.84 m3/s. Cropping pattern carried out with one year there are three cropping patterns, namely paddy - paddy - secondary crops. For the water requirements, enough can be fulfilled, but in August and September, where the planting period III for the secondary crops experiences a deficit. The method used to design flood discharge is the Nakayasu method. For the embankment construction and normalization is profitable.Keywords: River, Flood, Embankment, Thiessen, Comal